Multicriteria model for selecting TQM consultancy and certification services. Issue 7 (3rd October 2016) - Tavares de Aquino, Andre; Maciel de Melo, Renata
Abstract : Purpose: The purpose of this paper is to establish the need and the importance of adopting a structured model to support the decisions by using a multicriteria focus to guide drawing up a methodological framework. In addition, this study considers the maturity level of the organization, and the importance of continuous improvement after implementing ISO 9001. Design/methodology/approach: This study presents a scientific technical foundation of the qualifying and selection criteria of the consultancy and Accredited Certification Body (ACB) by using ISO standards, and the guidance document CB25, which is related to quality. Finally, a numeric application with realistic data is undertaken using the PROMETHEE II method, and the GAIA plan. Findings: The development of this study provides a new insight into the importance for selecting consultancy, and certification services in order to implement quality management systems within organizations. Research limitations/implications: The current study is limited to the quality management services. If necessary to apply the same model to other areas, it is necessary looking for documents and regulations of this field. In addition, this model is focussed on a model for small or medium companies, which are still trying to achieve a higher position in the sector, and do not have experts in quality management. Originality/value: The differential of this study is the foundation of the criteria for the proposed model. Other studies choose these criteria without any scientific basis. On the other hand, this study goes over many documents.